(3fXe GdLhGgQ ef GdOQ GdaGNQ aj hVY GdSGYGJ hNWhW aVd GdOGFQs - (3eLghds
(3ChdgG (B:s
(3HYO GdOjHGLg (B: (3adeG SCdfi HYV ENhGfi GdUGdMjf Cf CLeY dg QSGdg ai Yde GdhVY s
(3BNQgG (B:s
(3aEfi HGdYLR deYJQa hef GdNWC debJQa , hdfSCd Gddg GdYXje GdefGf Gdbhje GdCMSGf s
(3JHUQI GdYfhGf (B:s
(3fXes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B446 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B106 - (3U (B106 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs